2013
DOI: 10.1371/journal.pone.0065216
|View full text |Cite
|
Sign up to set email alerts
|

Frugivore Behavioural Details Matter for Seed Dispersal: A Multi-Species Model for Cantabrian Thrushes and Trees

Abstract: Animal movement and behaviour is fundamental for ecosystem functioning. The process of seed dispersal by frugivorous animals is a showcase for this paradigm since their behaviour shapes the spatial patterns of the earliest stage of plant regeneration. However, we still lack a general understanding of how intrinsic (frugivore and plant species traits) and extrinsic (landscape features) factors interact to determine how seeds of a given species are more likely to be deposited in some places more than in others. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
108
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(119 citation statements)
references
References 43 publications
4
108
1
2
Order By: Relevance
“…Conservation and management practices should focus on maintaining a frugivore assemblage as diverse as possible to allow for complementary seed dispersal (García & Martínez, 2012;Escribano-Avila et al, 2014), thus increasing the chance for a seed to reach favourable conditions and acus preferentially forage around the focal trees, sometimes in big flocks (T. iliacus), and fly short distances towards the neighbouring microhabitats (Martínez et al, 2008), thus most likely dispersing the seeds within forest patches. On the other hand, Turdus viscivorus tends to fly long distances and hence would disperse a substantial amount of seeds among forest patches (Jordano & Schupp, 2000;Martínez et al, 2008;Morales et al, 2013). Indeed, Morales et al (2013) showed that T. merula generated a more locally aggregated seed rain than T. viscivorus, who produced a more homogeneous seed rain at the landscape scale.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conservation and management practices should focus on maintaining a frugivore assemblage as diverse as possible to allow for complementary seed dispersal (García & Martínez, 2012;Escribano-Avila et al, 2014), thus increasing the chance for a seed to reach favourable conditions and acus preferentially forage around the focal trees, sometimes in big flocks (T. iliacus), and fly short distances towards the neighbouring microhabitats (Martínez et al, 2008), thus most likely dispersing the seeds within forest patches. On the other hand, Turdus viscivorus tends to fly long distances and hence would disperse a substantial amount of seeds among forest patches (Jordano & Schupp, 2000;Martínez et al, 2008;Morales et al, 2013). Indeed, Morales et al (2013) showed that T. merula generated a more locally aggregated seed rain than T. viscivorus, who produced a more homogeneous seed rain at the landscape scale.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Turdus viscivorus tends to fly long distances and hence would disperse a substantial amount of seeds among forest patches (Jordano & Schupp, 2000;Martínez et al, 2008;Morales et al, 2013). Indeed, Morales et al (2013) showed that T. merula generated a more locally aggregated seed rain than T. viscivorus, who produced a more homogeneous seed rain at the landscape scale. We observed similar patterns at our study sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large body mass species usually remove larger numbers of fruits and move seeds over longer distances than small species (Nathan et al, 2008;Wotton and Kelly, 2012;Morales et al, 2013). Although fruit-eating assemblages recorded in this study were entirely composed of small-sized birds (<100 g body mass), at least three medium-to-large bird species also dispersed P. parlatorei seeds in the undisturbed forest sites.…”
Section: Discussionmentioning
confidence: 55%
“…Their main frugivores are thrushes (Martínez et al, 2008): blackbird (Turdus merula), song thrush (T. philomelos) and mistle thrush (T. viscivorus), which are resident species, and fieldfare (T. pilaris), redwing (T. iliacus), and ring-ouzel (T. torquatus), which are over-wintering species in northern Spain. Despite sharing a strong taxonomic affinity, these thrush species may differ in their response to landscape structure and habitat features (Martínez et al, 2008;Morales et al, 2013).…”
Section: Study Systemmentioning
confidence: 99%